Resent study and prospect of ursolic acid and derivatives - Meng, Yanqiu; Yan, Zhaokai; Xia, Yan; Xinghua Qiu (Chemical Reagents, 2011)
Ursolic acid(UA,3beta-hydroxy-urs-12-en-28-oic acid),a pentacyclic triterpene compound, exists abundantly in the plant kingdom as the major constituent of medicinal herbs. UA has been reported to display a remarkable spectrum of biochemical activities to influence processes capable of controlling cancer development. The pleuripotent anti-tumor activities of UA have stimulated the experts to research actively in this field. This paper summarizes the modification and pharmacological activity of ursolic acid derivatives according to literature and reports both at home and abroad熊果酸(UA,3beta-羟基-乌苏烷型-12-烯-28-羧酸),五环三萜化合物,作为药草的主要成分,存在于丰富的植物王国中.据报道,UA具有广 谱的生物活性,调控和控制肿瘤细胞形成.UA多效性的抗肿瘤活性激发了专家们在这方面的积极研究,现综合国内外文献报道,对熊果酸结构修饰物及其药理活性 进行综述